Chlorothalonil Exposure Alters Virus Susceptibility and Markers of Immunity, Nutrition, and Development in Honey Bees. Issue 3 (23rd May 2019) - O'Neal, Scott T; Reeves, Alison M; Fell, Richard D; Brewster, Carlyle C; Anderson, Troy D
Abstract: Chlorothalonil is a broad spectrum chloronitrile fungicide that has been identified as one of the most common pesticide contaminants found in managed honey bees (Hymenoptera: Apidae: Apis mellifera L.), their food stores, and the hive environment. While not acutely toxic to honey bees, several studies have identified potential sublethal effects, especially in larvae, but comprehensive information regarding the impact of chlorothalonil on adults is lacking. The goal of this study was to investigate the effects of exposure to a field relevant level of chlorothalonil on honey bee antiviral immunity and biochemical markers of general and social immunity, as well as macronutrient markers of nutrition and morphological markers of growth and development. Chlorothalonil exposure was found to have an effect on 1) honey bee resistance and/or tolerance to viral infection by decreasing the survival of bees following a viral challenge, 2) social immunity, by increasing the level of glucose oxidase activity, 3) nutrition, by decreasing levels of total carbohydrate and protein, and 4) development, by decreasing the total body weight, head width, and wing length of adult nurse and forager bees. Although more research is required to better understand how chlorothalonil interacts with bee physiology to increase mortality associated with viral infections, this study clearly illustrates the sublethal effects of chlorothalonil exposure on bee immunity, nutrition, and development.